Temperature, precipitations and water balance trends in Maribor in the period 1876 – 2010 - Žiberna, Igor (Journal for Geography, 2011)
In this article are presented trends of temperature, precipitation, evapotranspiration and water balance for the meteorological station Maribor in the period 1876 – 2010. Analysed are the changes of monthly, seasonal and annual averages in observational sequences. Treated is also dynamics of trend changes in the observational period. Presented are connections between temperature trends and activity of the sun.